Autonomy of the Will in the Peruvian Civil Code of 1984: Commentary to Articles 2095 and 2096 - Delgado Menéndez, María Antonieta (1985)
The paper addresses the autonomy of will in the Peruvian Civil Code of 1984, focusing on articles 2095 and 2096. These allow the parties to freely choose the law applicable to a contract, without requiring a direct relationship between the selected law and the contract, which could lead to abuses such as the “internationalization” of contracts that are purely national. In this regard, the authors indicate that the intention of the parties to choose a certain law is due to their interest in achieving the application of a more permissive, or less prohibitive, law. They point out that the main problem lies in the fact that the Code does not contemplate the limitation of an “internationally permissible connection”. In addition, the authors emphasize that the legislator omits the express recognition of the figure of “fraud to the law”, which complicates the judicial action in cases of choice of more permissive foreign laws. However, despite these omissions, the paper emphasizes that Peruvian judges can apply certain legal principles to prevent the improper use of free will, thus protecting public order and the country's mandatory rules.